Safety of the "Inside-Out" Radiofrequency Ablation Technique for Rapid Localization of the Biceps Tendon in the Subacromial Space. Issue 2 (June 2016) - Saithna, Adnan; Longo, Alison; Leiter, Jeff; MacDonald, Peter; Old, Jason
Abstract : The purpose of this study was to evaluate a novel technique for localization of the long head of biceps tendon in the subacromial space. The procedure was documented in a cadaveric specimen and a subsequent surgical dissection was performed. The biceps tendon was quickly and easily located. Subsequent dissection demonstrated that no iatrogenic injury occurred to the rotator cuff. This technique offers rapid localization of the long head of biceps tendon through "inside-out" division of the transverse humeral ligament. It also offers a reduction in the risk of iatrogenic injury to the adjacent rotator cuff. Abstract : Supplemental Digital Content is available in the text.